Contemporary national utilization of extracorporeal cardiopulmonary resuscitation (ECPR) for out‐of‐hospital cardiac arrest. Issue 4 (13th February 2022) - Catalano, Michael A.; Pupovac, Stevan; Manetta, Frank; Kennedy, Kevin F.; Hartman, Alan; Yu, Pey‐Jen
Abstract: Objective: The utilization of extracorporeal membrane oxygenation (ECMO) during cardiopulmonary resuscitation (ECPR) has demonstrated promising evidence for the management of out‐of‐hospital cardiac arrest (OHCA). We aim to describe contemporary utilization and predictors of survival of patients receiving ECPR for OHCA. Methods: The National Inpatient Sample (NIS) was queried to identify hospital discharge records of patients aged ≥18 years who underwent ECPR from 2012 to 2017. Patients with an International Classification of Diseases, Tenth Revision, Clinical Modification diagnosis of cardiac arrest, admitted urgently and placed on ECMO on Day 0 of hospitalization, were selected. Patients with a primary diagnosis indicative of veno‐venous ECMO were excluded. Predictors of mortality were assessed using multivariable analyses. Results: There were 1675 cases of ECPR, increasing from 185 cases in 2012 to 400 in 2017 ( p < .001). Overall mortality was 63.3%, which remained stable over time ( p = .441). Common diagnoses included ST‐elevation myocardial infarction (39.1%), non‐ST‐elevation myocardial infarction (9.3%), and pulmonary embolism (13.7%). Percutaneous coronary intervention was performed in 495 patients (29.6%); coronary artery bypass grafting was performed in 125 patients (7.5%). In multivariable analysis, decreased age, female gender, and left ventricular (LV) decompression were associated with reduced mortality. Conclusion: Utilization of ECPR is increasing nationally with stable mortality rates. Younger age, female gender, and utilization of LV decompression were associated with increased survival.